INTEGRATING DEEP LEARNING IN LANGUAGE LEARNING: INSIGHT FROM THE LITERATURE - Nurmida Catherine Sitompul; Hariyanto; J. Priyanto Widodo (Magister Scientiae, 2025)
Deep learning in language learning has the potential to revolutionize learning with its ability to process complex data. This study aims to: 1) identify key trends in the use of deep learning, 2) explore the benefits and challenges of implementing deep learning in language learning, and 3) determine future research directions based on gaps found in the literature. This study uses a literature review approach. The study's findings indicate a notable trend in the application of deep learning to a number of languages learning domains, including online learning, sign language recognition, translation, language assessment, and personalized learning. Numerous advantages of deep learning were also noted by the study, including better learning outcomes, higher student engagement, and the creation of creative applications. The study did identify a number of difficulties, though, including the requirement for huge data, infrastructure constraints, and data privacy concerns. The researcher suggests that further research address the various gaps and maximize the potential of DL applications in learning.